Extraction and molecular detection of viral dsRNA from different infected plants - Delpasand Khabbazi, Afsaneh; Bashir, Nemat Sokhandan; Khabbazi, Saber Delpasand; Ighani, Hakimeh (Journal of Scientific Agriculture, 2017)
Extraction of viral double stranded RNA (dsRNA) from infected plants is helpful in identification of the viruses involved in infection. To date, there have been several methods developed to isolate dsRNA; however, type of the plant and virus is determinative in extraction efficiency. In this study we extracted dsRNA from different woody and herbaceous plants through a modified method which reduces the costs and time of extraction procedure. This method is based on different affinity of nucleic acids for the cellulose CF-11 in1X STE (Sodium chloride Tris EDTA) buffer containing 16 % ethanol. There is no phenol treatment or mini columns used in the isolation procedure. Extracted dsRNAs were identified by ribonuclease treatment and RT-PCR (Reverse Transcriptase-Polymerase Chain Reaction). We have applied the procedure on five different hosts representing Amaranthaceae, Vitaceae, Fabaceae and Rosaceae infected with four different viruses representing Secoviridae and Bromoviridae.